ANALYSIS OF INTERNAL CONTROL AND HUMAN RESOURCES ON FINANCIAL REPORTS - Dian Efriyenty; Argo Putra Prima; Risca Azmiana (LPPM Universitas Putera Batam, 2026)
Increasing population growth has led to an increasing number of children enrolling in prestigious schools or public schools. In this context, sound financial reporting is crucial for more transparent and accountable school financial management. Financial reports are prepared by finance staff in detail and supported by clear evidence. This is especially crucial for private schools that receive funding from various sources, such as tuition fees, foundation funds, and government assistance. However, some private schools still experience difficulties in preparing financial reports that meet standards and maintain high quality. This study involved 150 respondents. The results showed that human resources had no impact on the quality of financial reports. Meanwhile, the internal control system did.